2002
DOI: 10.1007/s00210-001-0526-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Na + required for the binding of dopamine, amphetamine, tyramine, and octopamine to the human dopamine transporter?

Abstract: The role of Na(+) in the recognition of blockers by the dopamine transporter is accomodated by a model with a cation site that overlaps with the blocker binding domain, and a distal Na(+) site that interacts with this cation site and perhaps with the blocker binding domain itself. The present study addresses the application of this model to the recognition of substrates by the dopamine transporter, focusing on conditions that should reveal a stimulatory effect, if present, of Na(+) on substrate binding. Recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…9). Because dopamine and other substrates have been shown to bind to the hDAT and related transporters with unchanged affinity even in the absence of Na ϩ (23)(24)(25), this observation strongly supports the idea that the protection of M371C observed only in the presence of Na ϩ is the consequence of a transport-associated conformational change. Data from our previous studies also argue against position 371 being a direct part of the substrate binding crevice.…”
Section: Ent Inhibition Of [supporting
confidence: 66%
See 1 more Smart Citation
“…9). Because dopamine and other substrates have been shown to bind to the hDAT and related transporters with unchanged affinity even in the absence of Na ϩ (23)(24)(25), this observation strongly supports the idea that the protection of M371C observed only in the presence of Na ϩ is the consequence of a transport-associated conformational change. Data from our previous studies also argue against position 371 being a direct part of the substrate binding crevice.…”
Section: Ent Inhibition Of [supporting
confidence: 66%
“…8), we were able to assess whether dopamine protection of this construct was Na ϩ -dependent. Transport is strictly Na ϩ -dependent, but increasing evidence suggests that dopamine and other substrates can bind to hDAT and related transporters with unchanged affinity even in the absence of Na ϩ (23)(24)(25). Accordingly, assessing the Na ϩ dependence of dopamine protection should enable us to distinguish between direct steric protection and a dopamineinduced conformational change that decreases the accessibility of M371C to MTSET.…”
Section: Mtset Inhibits [ 3 H]dopamine Uptake Of M371c and A399c Alsomentioning
confidence: 99%
“…As far as we know there are no reports of the interaction of Tris buffers with the GABA transport, but Li et al (2002) have reported that Tris allosterically interact with the substrate site of the dopamine transporter, which shares with the GABA transporters the fact that both belong to the SLC6 gene family (Gether et al, 2006). Furthermore, lead inhibited the uptake of GABA and potentiated the spontaneous release of GABA from motoneurons when Tris-HCl but not phosphate or carbonate buffers were used (Spence et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Protein content was determined by the DC protein assay (Bio-Rad). 3 H]DA uptake were obtained with the nonlinear computer fitting program KELL as described by us previously (17). IC 50 values for inhibitors were converted to K i values by the Cheng-Prusoff equation (18).…”
Section: Sds-polyacrylamide Gel Electrophoresis and Westernmentioning
confidence: 99%